Recent Advances in the Regulation of Brassinosteroid Signaling and Biosynthesis Pathways - Ye, H.; Li; L.; Yin, Y.
Brassinosteroids (BRs)play important roles in plant growth, development and responses to environmental cues. BRs signal through plasma membrane receptor BRI1 and co-receptor BAK1, and several positive (BSK1, BSU1, PP2A)and negative (BKI1, BIN2 and 14-3-3)regulators to control the activities of BES1 and BZR1 family ranscription factors, which regulate the expression of hundreds to thousands of genes for various BR responses. Recent studies identified novel signaling components in the BR pathways and started to establish the detailed mechanisms on the regulation of BR signaling. In addition, the molecular mechanism and transcriptional network through which BES1 and BZR1 control gene expression and various BR responses are beginning to be revealed. BES1 recruits histone demethylases ELF6 and REF6 as well as a transcription elongation factor IWS1 to regulate target gene expression. Identification of BES1 and BZR1 target genes established a transcriptional network for BR response and crosstalk with other signaling pathways. Recent studies also revealed regulatory mechanisms of BRs in many developmental processes and regulation of BR biosynthesis. Here we provide an overview and discuss some of the most recent progress in the regulation of BR signaling and biosynthesis athways.
Keywords: BIOSYNTHESIS; BRASSINOSTEROID; CROSSTALK; SIGNALING; TRANSCRIPTION